Penyuluhan Peran Lembaga Keuangan Syariah dalam Pengembangan UMKM di Desa Ngaran, Polanharjo, Klaten - Yazid, Afthon; Huda, Nurul; Anwar, Qosim Khoiri (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) has an important role in the village economy. One of the main factors in the development of MSMEs is access to adequate financing. Sharia Financial Institutions (LKS) have unique characteristics that can support the development of MSMEs with Islamic economic principles. This community service activity was carried out in Ngaran Polanharjo Village, Klaten, with the topic "Counseling on the Role of Sharia Financial Institutions in MSME Development". The implementation method used is counseling through presentations to the target audience about the role of LKS in facilitating MSME financing and discussions related to the realization of financial institutions around the community. The results of counseling show that LKS plays an important role in providing sharia financing to MSMEs in the village, with various financing products that are in accordance with sharia principles. In addition, LKS also provides guidance and assistance to MSME actors to improve the quality of their business. Thus, the role of LKS in the development of MSMEs in Ngaran, Polanharjo Village has a positive impact in improving the economic welfare of rural communities.